2010
DOI: 10.3945/ajcn.2010.29175
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake of n–3 long-chain polyunsaturated fatty acids and coronary events in Norwegian patients with coronary artery disease

Abstract: Background: Consumption of fish and n-3 (omega-3) long-chain polyunsaturated fatty acids (LCPUFAs) has been associated with reduced risk of coronary artery disease (CAD) mortality. Objective: The aim was to examine the relation between dietary intake of n-3 LCPUFAs or fish and risk of future coronary events or mortality in patients with well-characterized CAD. Design: This was a substudy of 2412 participants in the Western Norway B Vitamin Intervention Trial with a median follow-up time of 57 mo. Patients aged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 28 publications
2
27
0
2
Order By: Relevance
“…[1][2][3][4][5] In some studies no such association has been observed, [33][34][35] or an association has been seen for some but not for other cardiovascular outcomes. 36 Based on our English-language Medline search through October 2010, it is apparent that only a few studies have been Figure.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] In some studies no such association has been observed, [33][34][35] or an association has been seen for some but not for other cardiovascular outcomes. 36 Based on our English-language Medline search through October 2010, it is apparent that only a few studies have been Figure.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies (18,42) were excluded because the reference group was not the lowest exposure group. Two studies (7,20) were excluded because their reference fish intake categories were extremely high compared with other studies. One study (34) possessing a greatly different CHD baseline risk compared with the risk for the general population was ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 1 presents the detailed selection process. We identified twenty-nine potential studies (5)(6)(7)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44) . Seven studies (29,(31)(32)(33)37,43,44) were excluded because of their incomplete information on RR estimation or fish intake.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We estimated daily total intake of energy, as well as choline and betaine according to the USDA Database for the Choline Content of Common Foods (17 ), among 1939 patients who provided information on average dietary habits during the last year from food frequency questionnaires, as described elsewhere (18 ). We also calculated ␤-cell function, insulin sensitivity, and IR among 877 fasting patients without established type 2 diabetes at baseline with the computer-based updated homeostatic model assessment (HOMA2), as previously reported (19 ).…”
Section: Clinical and Biochemical Datamentioning
confidence: 99%